IMPROVING THE STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE PARAGRAPHS BY APPLYING THINK-TALK-WRITE STRATEGY - Yohana Faulina Tambunan; Amrin Saragih (LINGUISTICA, 2013)
ABSTRACT This study attempts Improving The Students’ Achievement In Writing Descriptive Paragraphs By Applying  Think-Talk-Write Strategy. This study was conducted by using classroom action research. The subject of the research was class XI IPA 1 SMA PARULIAN 1 Medan that consists of 28 students. The data of this study were obtained quantitatively through writing test which shows that the range of students who got score 75 to up is 92.85% and qualitatively from interview sheets, diary notes and observation sheets. Based on the diary notes, observation sheets and interview sheets, it was found that teaching-learning process ran well. Students were active, enthusiastic and interested in writing. The result of research showed that the Think-talk-write Strategy can improve students’ achievement in writing descriptive paragraph. It is suggested that teachers should use Think-talk-write strategy to improving students’ writing especially in writing descriptive paragraph. Keywords : Writing Descriptive, Think-Talk-Write Strategy, Parulian I Medan